(untitled) (Journal of the College of Education for Women, 2025)
The research aims to investigate the role of the university in building the child’s personality according to the opinions of a sample of teachers in the Applied Kindergarten’s workshop at the College of Education for Women, University of Baghdad. The researcher uses the descriptive approach and the case study approach presenting several questions including knowing the most prominent methods and practices followed by teachers of the Applied Kindergarten’s workshop, as well as the effect of educational programs in building the child’s personality that is in line with the cultural and social needs of children, in addition to its richness in cultural variables which made it a suitable spatial and human field of study. The researcher conducted a field study in this place for about nine months, during which she was able to investigate and learn many facts related to the research problem by conducting various interviews with teachers and participating with them in some of the activities they practice with children, which led to several results and conclusions, the most prominent of these conclusions were: Most teachers constantly provide guidance and advice to children and their parents, as there is a strong relationship between families and the institution to solve some of the problems related to them. The university’s role in building the child’s personality has a positive effect by providing conditions that are characterized by an educational and entertaining nature. The teachers of the Applied Kindergarten’s workshop are the main pillar in forming the child’s personality. The Applied Kindergarten’s workshop provides many educational programs that are in line with the children’s cultural and social needs, such as entertaining programs including music, drawing, and games and educational programs such as teaching them the alphabet and reading the Qur’an, etc.